Application of the Concept of Multi-phase Experience to Wait Management in Restaurant Services - Kim, Jong (Routledge, 2011)
The main purpose of this study was to develop wait management strategies for different stages of a dining experience and to test the effects of these strategies on customer satisfaction and their future behavioral intentions (e.g. loyalty and word-of-mouth). The stages included in this study were pre-process, in-process and post-process. To test successfully the effects of wait management strategies applied to each dining stage, an experimental study was conducted using a 2 (duration information versus no treatment) × 2 (free appetizer versus no treatment) × 2 (discount coupon for future purchase versus no treatment) between-subjects design in which subjects were provided with a written scenario that simulated real-life experience. Multivariate analysis of covariance was used to examine the mean differences between treatment groups and no-treatment groups while controlling individuals' level of tolerance with the length of waiting time. The results support the hypotheses that management strategies at in-process and post-process stages are effective in enhancing customer satisfaction as well as behavioral intentions. In particular, providing a discount coupon achieved the most significant effect among the proposed wait management strategies.